Peningkatan Aktivitas dan Prestasi Belajar Siswa melalui Penerapan Metode Pembelajaran Kooperatif Group Investigation - Siti Juwariyah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2018)
This study aims to determine the implementation of cooperative learning method group investigation can increase activities and student achievement in demographic and environmental materials beings subjects of Natural Science (IPA) in the class IX C MTs Negeri 1 Bantul. The study was conducted in two cycles. Cycle I consisted of 2 meetings, and cycle II consisted of 3 meetings. The results showed that the implementation of cooperative learning method group investigation can increase activities and student achievement in demographic and environmental materials beings subjects of IPA in the class IX C MTs Negeri 1 Bantul. Increasing the activities of student learning based on data from the observation are enaugh category in cycle I, and high category in cycle II. Increasing the activities of student learning based on data from the questionnaire are: 64,82% in early learning, 67,58% in cycle I, and 75,11% in cycle II, the entire cycle in the high category. Improving student achievement can be seen from the mean, the number of student who completed, and the clasical completeness. The mean increased from 39,4 at the placement test, 79,2 in cycle I, and 83,9 in cycle II. The number of students increased from no student get completed the placement test, is 23 students in cycle I, and 30 students in cycle II. Clasical completeness increased from 0% at the placement test became 71,88% in cycle I, 93,75% in cycle II.